2019
DOI: 10.18502/ijph.v48i3.886
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of the Potential Drug-Drug Interactions Involving Anticancer Drugs in China: A Retrospective Study

Abstract: Background: To survey the prevalence of potential drug-drug interactions (DDIs) between anticancer drugs and non-anticancer drugs and evaluate the risk factors associated with these drug-drug interactions in China. Methods: All discharged patients in the Department of Oncology were collected from Jun to Dec in 2016 with the Hospital Information System of the Chinese people’s Liberation Army General Hospital. Drugs were screened for interactions by Micromedex solutions database. Descriptive statistics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…In Brazil, it is known that there is wide use of herbal medicines and medicinal plants, which is due to historical and cultural aspects and to the broad availability of species in our country. Thus, many patients reported drinking teas to manage adverse reactions during chemotherapy treatment 11,18 . This is relevant information for the entire multiprofessional team identified in this study, as the therapeutic index of antineoplastic chemotherapeutics is oftentimes narrow and herbal medicines and medicinal plants can alter the expression of several enzymes related to the biotransformation of medications; therefore, drug interactions can have undesirable consequences and may even compromise the person's life in some cases 19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, it is known that there is wide use of herbal medicines and medicinal plants, which is due to historical and cultural aspects and to the broad availability of species in our country. Thus, many patients reported drinking teas to manage adverse reactions during chemotherapy treatment 11,18 . This is relevant information for the entire multiprofessional team identified in this study, as the therapeutic index of antineoplastic chemotherapeutics is oftentimes narrow and herbal medicines and medicinal plants can alter the expression of several enzymes related to the biotransformation of medications; therefore, drug interactions can have undesirable consequences and may even compromise the person's life in some cases 19 .…”
Section: Resultsmentioning
confidence: 99%
“…They can occur throughout the treatment and can be with medications that were already used by the patient and/or others that are added during course of the treatment. This issue is of major importance due to the intrinsic characteristics of chemotherapy drugs, such as their narrow therapeutic index and, therefore, drug interactions can increase toxicity or decrease their effectiveness, compromising treatment and patient safety 11 .…”
Section: Introductionmentioning
confidence: 99%
“…41 A Chinese study reported a 97.02% severity level of drug-drug interactions in cancer patients. 51 In addition, 67% severe and 26.9% moderate drug-drug interactions were observed among cancer patients undergoing chemotherapy. 52 The findings of the current study suggested a higher incidence of potential drug-drug interactions among gastrointestinal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…DDI, which causes 4% of cancer death, is of major concern in oncology [ 5 ]. This is owing to the inherent toxicity/narrow therapeutic index of anticancer agents, their intra- and inter-individual variability, and their simultaneous administration along with different drugs to cancer patients [ 6 11 ]. DDI can be manifested at the pharmacokinetic (PK) and/or the pharmacodynamics (PD) level or a combination of mechanisms of the drug itself or a combination of drugs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%